The Competence of Balinese Cattle Farmers in Oeledsala Village, Taebenu District, Kupang Regency - Fadillah Andre Kurniawan; Siti Azizah (Agriwar Journal, 2024)
This research is located in Oeledsala Village, Taebenu District, Kupang Regency. This research aims to provide additional information for Bali Cattle breeders to be able to increase income by using a more targeted system and it is also hoped that the results of this research can help the government make decisions and policies in economic development for Bali Cattle breeders. The respondents we interviewed were 50 Balinese cattle breeders in Oeledsala Village. Data collection was carried out from 15 September 15, 2023, to 10, 2023. The data taken in this research were the level of technology (X1), Extension Experience (X2), and Breeder Competency (Y). The data were analyzed using descriptive analysis and regression analysis. The results of the research show that both the level of technology used by breeders and the experience of participating in extension program have a positive impact on increasing the potential of Bali cattle breeders, however, based on the hypothesis testing carried out, the variable that has a significant influence between the two independent variables used in this research is the variable of experience following livestock extension (X2) because it has a p-value < 0.05).